Creative Strategy of the Production Team in Developing Built-In Advertisements for Trans TV's Insert Program - Nada Nisrina; Filosa Gita Sukmono; Dhimas Aryo Vipha Ananda (Jogjakarta Communication Conference (JCC), 2026)
The conventional television industry is currently facing significant challenges due to rapid advances in digital technology that are transforming audience consumption patterns. Trans TV’s infotainment program Insert responds to these dynamics through a built-in advertising strategy or ad inserts to maintain revenue without disrupting the viewer experience. This study aims to analyze the creative strategies employed by the “Insert” production team in designing in-program advertisements to ensure they appear natural and align with the program’s character. The method used is descriptive qualitative research within a constructivist paradigm. Data were collected through in-depth interviews, observations, and documentation with key informants, including assistant producers, scriptwriters, and the marketing team. The results indicate that creative strategies are implemented through four key indicators: message planning based on the integration of content knowledge and procedures; stimulating audience attention through neutral opening techniques and the selection of relevant characters; integrating products into the storyline to blend with the narrative; and managerial coordination to maintain a balance between commercial interests and production aesthetics. This study concludes that a subtle sales approach is effective in maintaining program integrity, despite challenges arising from the tension between the production team’s creative ideals and the client’s commercial constraints. Theoretically, this study reinforces that the message-building process in the media industry is heavily influenced by organizational filters and market pressures.